2015
DOI: 10.5455/ijmsph.2015.2211201494
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding clonidine versus fentanyl to intrathecal bupivacaine on spinal block characteristics in orthopedic procedures: A double blind controlled study

Abstract: Opioids and local anesthetics administered together intrathecally are known to have synergistic analgesic effects. [1] Fentanyl, a short-acting lipophilic opioid, was administered intrathecally along with local anesthetics by Belzarena. [2] Clonidine, an α 2 adrenergic agonist, has been used as an antihypertensive agent for many years. Recently its desirable anesthetic properties in human have been highlighted, which include reducing anesthetic requirements, improving hemodynamic stability, and providing analg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…They concluded that addition of intrathecal clonidine to hyperbaric bupivacaine was more advantageous than fentanyl with special regard to its analgesic properties. [ 19 ] Singh et al . evaluated the effect of addition of intrathecal clonidine to hyperbaric bupivacaine on postoperative pain after caesarean section and has shown that the duration of postoperative analgesia increases significantly on adding 75 μg clonidine to 2 ml of hyperbaric bupivacaine without any increase in maternal side effects.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that addition of intrathecal clonidine to hyperbaric bupivacaine was more advantageous than fentanyl with special regard to its analgesic properties. [ 19 ] Singh et al . evaluated the effect of addition of intrathecal clonidine to hyperbaric bupivacaine on postoperative pain after caesarean section and has shown that the duration of postoperative analgesia increases significantly on adding 75 μg clonidine to 2 ml of hyperbaric bupivacaine without any increase in maternal side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Tilkar et al conducted a prospective study to differentiate between the effects of fentanyl versus clonidine when added to intrathecal bupivacaine in spinal anesthesia. They concluded that addition of intrathecal clonidine to hyperbaric bupivacaine was more advantageous than fentanyl with special regard to its analgesic properties [29] . Singh et al evaluated the effect of addition of intrathecal clonidine to hyperbaric bupivacaine on postoperative pain after caesarean section and has shown that the duration of postoperative analgesia increases significantly on adding 75 μg clonidine to 2 ml of hyperbaric bupivacaine without any increase in maternal side effects.…”
Section: Discussionmentioning
confidence: 99%
“…According to some study, even at higher dose of clonidine (450 µg) only in intrathecal, didn't result muscle weakness and motor block [28] , but combination to spinal bupivacaine caused significant enhancement of the strength and duration of motor block [29,30]. Tilkar et al study compared clonidine and fentanyl added to intrathecal bupivacaine and reached as conclusion of clonidine was more helpful than fentanyl in pain-relieving properties [31].…”
Section: Discussionmentioning
confidence: 99%